Reduction in the utilization of prednisone or methotrexate in Canadian claims data following initiation of etanercept in pediatric patients with juvenile idiopathic arthritis - Majed Khraishi (Pediatric Rheumatology Online Journal, 2019)
Abstract Background In adult patients with arthritis, use of the tumor necrosis factor (TNF) inhibitor etanercept (ETN) is often associated with a reduction in the utilization of co-medications, particularly steroids. Comparatively little is known about the utilization of co-medications when ETN is initiated in pediatric patients with juvenile idiopathic arthritis (JIA). Methods This study analyzed Canadian longitudinal claims level data spanning January 2007 to April 2017. Data were collated from the IQVIA Private Drug Plan, Ontario Public Drug Plan, and the Quebec Public Drug Plan (Régie de l’assurance maladie du Québec) databases. Patients < 18 years of age were indexed when filling a prescription for ETN between January 2008 and January 2016. Those who met the inclusion and exclusion criteria were assessed for methotrexate (MTX), and prednisone (PRD) use in the 6 months prior to and 12 months following initiation of ETN. Results Longitudinal claims data for 330 biologic-naive pediatric patients initiating ETN therapy were included. The majority of patients were female (67%), aged 10–17 years (64%), and with a drug history consistent with JIA (96%). Most patients were from Quebec (36%) or Ontario (33%). Dosing of ETN was weight-based with a mean dosage over the first year of 31 mg per week. ETN dosing was relatively consistent over the first year. In total, 222 (67%) patients did not use MTX and 223 (68%) did not use PRD before or after starting ETN. A total of 17% (18/103) of MTX-treated and 50% (46/92) of PRD-treated patients discontinued use of those medications upon initiation of ETN treatment. In patients continuing MTX or PRD, significant reductions in the weekly dosage from 14.3 to 6.8 mg per week for MTX and from 56 to 23 mg per week for PRD were observed (P < 0.01). Conclusions This study of Canadian claims-level data is the first large prespecified analysis of co-medication utilization following the initiation of ETN therapy in pediatric patients. A decline in both MTX and PRD use and dosage was observed and may be associated with benefits related to safety, tolerability, and overall healthcare costs.